Perencanaan Bangunan Pengendali Banjir (Kanal) Di Das Air Bengkulu - Wahyu Yulianto; Meilani Belladona; Jawoto Sumajaya (MAJALAH TEKNIK SIMES, 2021)
Abstract The Air Bengkulu River Basin experiences a frequency of flooding twice a year due to the increase in water discharge during the rainy season. The purpose of this study is to determine the amount of peak discharge of the Air Bengkulu River and make a design of floodway control buildings dimensions in the Air Bengkulu River Basin. Rainfall data used in the purposes of this study are rainfall data for the last 10 years (2010-2019). Rainfall analysis plans calculated by statistical methods. The analysis of the planned flood peak discharge was calculated using the Nakayasu Synthetic Unit Hydrograph method with the results of the peak discharge of the Air Bengkulu River for the 2nd, 5th, 10, 20, 25, 50 and 100 year anniversary periods, respectively 557.68 m3/s; 732.85 m3/s; 845.18 m3/s; 955.15 m3/s; 978.80 m3/s; 1074.35 m3/s; and 1166.71 m3/s. Flood canal design analysis is calculated using the manning equation method (try error) using a return period of 25 years with a discharge of 955.15 m3/s; circular canal with a cross-sectional diameter of 18.5 m; with a water level of 14.68 m and a height of 3.82 m; while the canal is square in shape with a base width of 25 m; water level of 5.55 m; and height of 1.45 m guard; able to accommodate the debit plan return period of 25 years.